SPORTS SCIENCES AND MULTICULTURALISM - EDUCATIONAL AND PROFESSIONAL IMPACT - Danica Pirsl; Nenad Zivanovic; Tea Pirsl (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
The aim of the paper is to familiarize the sports sciences educators to the pedagogic concept and professional benefits and awareness of multicultural education if implemented in sports sciences curricula, especially in the efforts to obtain international transparency through sports science literature writing and publishing. Data Sources were textbook chapters and articles searched through the archives of Diversity Digest and Academic Medicine for the years 2000 to 2005 with the key words multiculturalism, diversity, cultural competence, education, and learning. Synthesized data were used to present a rational argument for the inclusion of a critical pedagogy into the field of sports science education. The infrastructure in the professional field of sports sciences, review of the literature on critical multicultural theory and pedagogy and the potential cognitive and intellectual implications of diversity and multicultural education were analyzed. Conclusions/Recommendations focus on possible various and creative strategies for implementing a multicultural agenda in sports sciences curricula and on the analysis of the associated benefits and outcomes of such educational strategies.